In vivo study of endometriosis in mice by photoacoustic microscopy. Issue 1 (11th February 2014) - Ding, Yichen; Zhang, Mingzhu; Lang, Jinghe; Leng, Jinhua; Ren, Qiushi; Yang, Jie; Li, Changhui
<x xml:space="preserve">Abstract</x> Endometriosis affects 6‐10% of women of reproductive age, and usually requires an invasive method with an over‐6‐year mean latency from onset of symptoms to definitive diagnosis. It is the first time that photoacoustic microscopy has been used to study this disease, by its specific absorption spectrum. As endometriosis lesions are hazardous for females, this work may suggest a novel application of photoacoustic tomography. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>